Conscious consumption, environment and sustainable development: analysis of decision-making based on heuristics - Nespolo, Daniele; Borelli, Verena Alice; Fidelis, Andréa Cristina Fermiano; Machado, Sandro Manoel; Olea, Pelayo Munhoz; Rocha, Jefferson Marçal da (Revista de Administração da UFSM, 2016)
Environment and sustainable development, in recent years, have been considered relevant and present issues in society because of the impact they cause in our daily lives. Therefore, the aim of this study was to analyze, through heuristics, the decision-making of individuals related to the preservation of the environment. Developed for this, a kind of applied research with a quantitative and exploratory approach, making use of bibliographic research and data collection through a questionnaire based on the Likert scale, with five points. To perform the analysis of the data, using IBM SPSS Statistics 20 software, were applied descriptive statistics and simple correlation. It was evident that the highest correlations are related to the understanding and comprehension of the issues addressed in this study and the smaller are related to the behavior of individuals on environmental issues. Thus, it can be affirmed that there is an understanding of the environmental and sustainability issues that emerge in the current context, however are still required attitudes towards environmental actions.